Exploring emotional ties: Insights into intrinsic motivations and casual gaming intentions - Joliss Helen George; V.K. Ranjith (Acta Psychologica)
This research explores the relationship between casual gamers' intrinsic motives and gameplay intentions. Drawing upon the attachment theory, this study investigates the interaction effect of attachment between intrinsic gaming motives and intentions. The study adopted a cross-sectional survey design through an online survey. A total of 390 students from a university located in the southern state of India participated in the survey. The proposed model was examined using Confirmatory Factor Analysis (CFA) and the study's hypotheses were tested using partial least square-structural equation modeling (PLS-SEM). The study contributes with its three important findings: First, gamers' hedonic motives, flow experience, and attachment to esports had a significant direct and positive association with gameplay intentions. Second, attachment to esports partially mediates the hedonic motive-gameplay intention and flow-gameplay intentions relationship, while fully mediating the relationship between fantasy and gameplay intentions. Third, escape had neither a direct nor an indirect impact on gameplay intentions. This study builds on the esports literature from casual gamers' psychology perspective. Furthermore, the findings may help game designers and marketers to develop more effective strategies to engage their target audience. Sports and leisure research has highlighted players' gaming motives and intentions often focusing on technology acceptance. Nevertheless, the affective element that motivates players to participate in casual gaming remains largely untapped. This study explores the role of casual players' attachment to esports and its influence on their intrinsic motives and gaming intentions.